Modelling Aggregate Demand for Labour: A Reply to Dowrick and Wells - MacDonald, Garry (Blackwell Publishing Asia, 2004)
Dowrick and Wells (2004) have attempted to point to what they see as a number of fundamental misinterpretations in a recent paper by Lewis and MacDonald (202) estimating demand for labour in Australia. However, it is argued that it is a particular assumption about a nominal price setting that leads to their results being different from that of the standard literature on labour demand. When the usual assumption are adopted, the results of Lewis and MacDonald (2002) hold and, therefore, are correct.